Carbon reduction activism in the UK: lexical creativity and lexical framing in the context of climate change - Nerlich, Brigitte; Koteyko, Nelya (Taylor and Francis, 2009)
This article examines discourses associated with a new environmental movement, “Carbon Rationing Action Groups” (CRAGs). This case study is intended to contribute to a wider investigation of the emergence of a new type of language used to debate climate change mitigation. Advice on how to reduce one's “carbon footprint,” for example, is provided almost daily. Much of this advice is framed by the use of metaphors and “carbon compounds”—lexical combinations of at least two roots—such as “carbon finance” or “low carbon diet.” The study uses a combination of tools from frame analysis and lexical pragmatics within the general framework of ecolinguistics to compare and contrast language use on the CRAGs' website with press coverage reporting on them. The analysis shows how the use of such lexical carbon compounds enables and facilitates different types of metaphorical frames such as dieting, finance and tax paying, war time rationing, and religious imperatives in the two corpora.